(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
The experiment was conducted to investigate the effect of mixed supplementation of turmeric and cinnamon powder on the performance and egg quality of Japanese quail. This study entailed of five treatments with four replications of 20 quails each established in a completely randomized design. The treatments consisted of T0 (control), T1 (10 g cinnamon + 10 g turmeric)/kg of feed, T2 (10 g cinnamon + 20 g turmeric)/kg of feed, T3 (20 g cinnamon + 10 g turmeric)/kg of feed, and T4 (20g cinnamon + 20g turmeric)/kg of feed. Feed intake, body weight, feed conversion ratio, egg production, yolk weight, white weight, shell weight, yolk color index, and cholesterol level were among the parameters that were examined. In addition, the percentages of quails that reached maturity at 42 days of age were recorded. The obtained results indicated that supplementing the diet with a mixture of turmeric and cinnamon reduced feed intake and significantly (P<0.05) improved the feed conversion ratio. The average body weight of quails at 42 days did not differ significantly (P>0.05) among the various treatment groups. The dietary supplementation of turmeric and cinnamon, significantly increased the egg production percentage, egg yolk weight and significantly (P<0.05) decreased egg yolk cholesterol level. Therefore, it is recommended that incorporating 20g of turmeric and 20g of cinnamon powder per kg of feed can enhance the performance and egg quality of Japanese quails. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 305-314